Tinjauan Yuridis Terhadap Shopee Pinjam Pada Marketplace Berdasarkan Ekonomi Islam - Wiwin Muchtar Wiyono; Eti Mul Erowati; Ferryani Krisnawati (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
Shopee borrows from the marketplace, which is one of the products offered by Shopee to give to users so they can get cash loans with easy procedures. The reciprocity that users must provide is by paying the loan in installments every month. In this case, Shopee will pay interest to borrowers and if there is a delay in repaying the loan, the borrower will be subject to a fine. The research carried out was field research, this research was descriptive in nature, data analysis in this research used a qualitative descriptive approach. The approach in this research is to obtain and collect data directly or directly from shopee loan users. Shopee's practice of borrowing from the Shopee application is that loans start from 500,000 – 1,500,000.- with monthly installments and with different interest starting from 10%-30% and if you are late in paying you will be subject to a fine of 3% of the nominal amount to be repaid. Review of Islamic Economic Law regarding the practice of borrowing hope from the Shopee application applies qardh conditions, namely the existence of borrowers, lenders, goods/debts, ijab and qabul. But in this practice there is interest which gives rise to usury, so this practice is a practice that is clearly prohibited in Islam. Based on this research, it can be stated that the practice of debts and receivables in the Shopee loan application including usury. The reason is because interest is in addition to the principal of the loaned capital. Keywords: Shopee Borrow, Marketplace, Islamic Economy